Implementation of the Integrated Entrepreneurship Learning Model on Entrepreneurial Interest Through Motivation as a Mediating Variable - Khusnul Fikriyah; Anik Lestari Andjarwati; Saino Saino; Mariana Mariana; Lintang Venusita; Dea Andani Nur’aini (International Journal of Emerging Research and Review, 2026)
Objective: The Entrepreneurship Learning Model implemented at the Faculty of Economics and Business (FEB), Surabaya State University (Unesa), is an integrated learning model. This model aims to enhance students’ entrepreneurial interest through entrepreneurial motivation. Method: This study employs a quantitative research method. Data were collected through questionnaires, with respondents consisting of FEB Unesa students, and the data were obtained in 2024. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Results: The results indicate that: 1.) the integrated learning model implemented at FEB has a significant effect on students’ entrepreneurial motivation; 2.) entrepreneurial learning motivation has a significant effect on entrepreneurial interest; and 3.) the learning model has a significant indirect effect on entrepreneurial interest through motivation. Novelty: These findings have several important implications. From an academic perspective, the development of entrepreneurship curricula in higher education should not rely solely on formal classroom learning (credit-based courses) but must also be supported by non-formal learning activities such as training, seminars, practical experiences, and the development of a real entrepreneurial ecosystem. Practically, these results also support the Merdeka Belajar Kampus Merdeka (MBKM) policy, particularly in designing programs such as Wirausaha Merdeka and entrepreneurship internships.